1990 Winter Simulation Conference Proceedings 1990
DOI: 10.1109/wsc.1990.129581
|View full text |Cite
|
Sign up to set email alerts
|

Effective cost modeling on the factory floor: Taking simulation to the bottom line

Abstract: STATEMENT OF PURPOSEThe purpose of this panel is to discuss the effective implementation of cost modeling methodologies on the factory floor. Our target audience is industrial and manufacturing engineers that are experienced in simulation modeling and are familiar with manufacturing cost issues. MANUFACTURING COST ACCOUNTING -THE ARENAIn todays competitive manufacturing environment, engineers are often required to provide performance analysis memcs in terms of actual dollarsthe bottom line. No longer can the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many authors have demonstrated the weakness of the traditional accounting system in manufacturing operations (Zuk et al , 1990; Greenwood and Reeve, 1992; Cooper and Kaplan, 1998; Adler et al , 2000; Brimson, 2007).…”
Section: Mistakes Introduced By Traditional Accounting: First Examplementioning
confidence: 99%
“…Many authors have demonstrated the weakness of the traditional accounting system in manufacturing operations (Zuk et al , 1990; Greenwood and Reeve, 1992; Cooper and Kaplan, 1998; Adler et al , 2000; Brimson, 2007).…”
Section: Mistakes Introduced By Traditional Accounting: First Examplementioning
confidence: 99%
“…A simulation can also be used as a basis for defining and calculating these costs as the product moves through the system. These costs may be associated with stations in the simulation model through which the product passes and may include the contribution to cost of added materials, of set-up transactions, of frequency in handling, and other detailed considerations that realistically add to the cost of manufacturing (Zuk et al 1990). …”
Section: Simulation-based Cost Accountingmentioning
confidence: 99%